2019
DOI: 10.1002/dvg.23278
|View full text |Cite
|
Sign up to set email alerts
|

Insights into retinoic acid deficiency and the induction of craniofacial malformations and microcephaly in fetal alcohol spectrum disorder

Abstract: Summary Fetal Alcohol Spectrum Disorder (FASD) is a set of neurodevelopmental malformations caused by maternal consumption of alcohol during pregnancy. FASD sentinel facial features are unique to the disorder, and microcephaly is common in severe forms of FASD. Retinoic acid deficiency has been shown to cause craniofacial malformations and microcephaly in animal models reminiscent of those caused by prenatal alcohol exposure. Alcohol exposure affects the migration and survival of cranial neural crest cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 345 publications
(538 reference statements)
0
37
0
3
Order By: Relevance
“…Interestingly, ethanol-sensitive signaling pathways detected during early embryogenesis were Wnt, Notch, and retinoic acid. Ethanol-induced dysregulation of retinoic acid signaling pathway was reported earlier 16,17,19,[38][39][40][41] . Our studies examining the heart and the eye in ethanol-treated embryos identified disruption of Wnt, Notch, retinoic acid and Bmp signaling pathways during organogenesis [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, ethanol-sensitive signaling pathways detected during early embryogenesis were Wnt, Notch, and retinoic acid. Ethanol-induced dysregulation of retinoic acid signaling pathway was reported earlier 16,17,19,[38][39][40][41] . Our studies examining the heart and the eye in ethanol-treated embryos identified disruption of Wnt, Notch, retinoic acid and Bmp signaling pathways during organogenesis [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 56%
“…The variability of phenotype in this congenital disease is due to differences in the timing and amount of alcohol exposure during embryogenesis. Bird, rodent, frog, and zebrafish models of fetal alcohol syndrome utilize different exposure times and at various stages to understand the mechanisms underlying tissue damage (Joya, Garcia-Algar, Vall, & Pujades, 2014;Kiecker, 2016;Petrelli, Bendelac, Hicks, & Fainsod, 2019;Riley et al, 2011;Sulik, Johnson, & Webb, 1981;Sulik, Lauder, & Dehart, 1984;Zhang et al, 2014). The original hypothesis proposed that ethanol is a competitive inhibitor of the aldehyde dehydrogenase enzymes that are also important in the conversion of retinol to RA (Deltour et al, 1996;Duester, 1991).…”
Section: Congenital Craniofacial and Ocular Diseases Resulting Frommentioning
confidence: 99%
“…Targets of RA signaling provide promising candidates for elucidating the mechanism by which RA may be involved in FASD. Top among these is Sonic Hedgehog (Shh) signaling (Petrelli, Bendelac, Hicks, & Fainsod, 2019). Loss of Shh pathway members results in holoprosencephaly (HPE) spectrum consisting of defects in neural tube development, loss of midline craniofacial structures, and neural crest-specific cell death (Chiang et al, 1996;Cordero et al, 2004;Eberhart et al, 2006;Jeong, Mao, Tenzen, Kottmann, & McMahon, 2004;Pan, Chatterjee, & Gerlai, 2012;Roessler & Muenke, 2010;Wada et al, 2005).…”
Section: Alcohol-sensitive Genes In Animal Modelsmentioning
confidence: 99%